2019
DOI: 10.1080/20961790.2018.1557386
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem chest computed tomography for the diagnosis of drowning: a feasibility study

Abstract: It may be difficult to distinguish the cause of death in drowning cases without specific findings. The aim of this study was to explore the forensic value of thoracic postmortem computed tomography (PMCT) using routine images and three-dimensional (3D) image reconstructions. The imaging data of PMCT examinations of six drowning cadavers, aged 21-54 years, were analyzed. Twelve victims of sudden death from coronary artery disease (CAD) were chosen as a control group. After 3D bilateral lung images were reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…When a forensic pathologist deals with a body recovered from the water, it remains challenging to identify the cause of death, especially distinguishing drowning from other deaths [1]. A fresh drowning corpse generally has some significant signs such as pale skin and froth in the mouth and nostrils.…”
Section: Introductionmentioning
confidence: 99%
“…When a forensic pathologist deals with a body recovered from the water, it remains challenging to identify the cause of death, especially distinguishing drowning from other deaths [1]. A fresh drowning corpse generally has some significant signs such as pale skin and froth in the mouth and nostrils.…”
Section: Introductionmentioning
confidence: 99%
“…This study was the first of its kind to our knowledge, using PMCT data to evaluate a range of reconstruction setting for postmortem conditions. Although earlier publications have suggested the use of PMCT specific reconstructions [ 12 ], or applied reconstructions for analysis of PMCT scans [ 37 , 38 ], this is the first study systematically analyzing the usefulness of reconstructions designed for PMCT purposes.…”
Section: Discussionmentioning
confidence: 99%
“…They compared these animal models of hemorrhagic shock and mechanical asphyxia. The CT values indicated that the lungs volumes were significantly higher (P < 0.05) thus signifying that the virtopsy characteristics can reflect the important features in case of antemortem drowning [9,11].…”
Section: Application Of Virtopsy In Forensic Sciencesmentioning
confidence: 90%